Pengaruh Risiko Kredit, Likuiditas, Permodalan, Ukuran Bank, dan Kinerja Intermediasi terhadap Profitabilitas Bank Pembangunan Daerah di Indonesia - Vicka Pramudya Putra; Heri Faisal Harahap; Chairilisa Azzahra (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study analyzes how credit risk, liquidity, capital adequacy, bank size, and intermediation performance influence the profitability of Regional Development Banks in Indonesia. Profitability is proxied by Return on Assets, while credit risk is proxied by Non-Performing Loan, liquidity by Loan to Deposit Ratio, capital adequacy by KPMM/CAR, bank size is represented by the natural logarithm of total assets, while intermediation performance by Net Interest Margin and loan distribution. This study uses a quantitative approach based on quarterly panel data from 17 Regional Development Banks during the 2018–2025 period. The data are analyzed using panel data regression in Stata, with three estimation approaches: the Common Effect Model, Fixed Effect Model, and Random Effect Model. The model selection test shows that the Fixed Effect Model is the most suitable estimation model. The findings show that all independent variables simultaneously affect ROA. Partially, NIM positively and significantly affects ROA, whereas NPL has a significant negative effect on ROA. Meanwhile, LDR, KPMM, bank size, and loan distribution do not significantly affect ROA. These results suggest that BPD profitability is more strongly determined by credit quality and the ability to generate net interest income.